The Impact of Family Assistance on The Reduction of Elderly Depression in Rural Communities - Herry Prasetyo; Handoyo Handoyo; Hartati Hartati (Universitas Padjadjaran, 2023)
Due to their limitations, adult family members have the responsibility and task of supporting the elderly in theirdaily lives. Family members who accompany older people who are depressed will help them recover quickly andimprove their quality of life. The purpose of this study was to identify the role of family members in supportingthe elderly who were depressed. The study’s benefits include ensuring that the elderly stay productive in old age,independent, and happy in their everyday activities. The research approach was a quantitative study employing aquasi-experimental design with a pre-post test and no control group design. The participants in this study were allolder persons suffering from depression in a rural village in Banyumas Regency. The sampling technique used wassimple random sampling with a population of 245 senior persons. According to the inclusion criteria, respondents inthis study got a total of 36 elderly. The Geriatric Depression Scale (GDS) was the tool used to assess the amount ofdepression in the elderly. The GDS questionnaire was used to obtain research data on elderly individuals attendingintegrated service post activities. The t-test was used to analyze the data, and the results produced with p = 0.000are = 0.05. The findings of this study suggested that family help had a substantial effect on the amount of depressionexperienced by the elderly. As a result, the family members must support the elderly in their daily activities.